Analisis Format, Substansi Dan Yuridis Amandemen Undang-Undang Dasar 1945 (Lex Jurnalica, 2006)
The Constitution of 1945 (Undang-Undang Dasar 1945) which was passed by PPKI (Panitia Persiapan Kemerdekaan Indonesia) on August 18, 1945 was a provisional Contitution quality. Because of it, Soekarno who the Indonesia first President hoped the Contitution of 1945 soon could be perfected. But Indonesians history showed for amendment of Constitution of 1945 just for 1999 until 2002. Being amandment of Constitution which be able to desire for accomodating reformation prosecution likes about restruction of exsecutive power, recognition and protection of the human rights, and law enforcement. This article discuss about juridical, substance, and form analysis of the amendment of the Constitution of 1945Key words: Juridical, substance, form analysis of the amendment of theConstitution of 1945